2018
DOI: 10.1007/s00127-018-1613-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of assertive community treatment among adolescents

Abstract: In the absence of a copyright statement, users should assume that standard copyright protection applies, unless the article contains an explicit statement to the contrary. In case of doubt, contact the journal publisher to verify the copyright status of an article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Seven studies were excluded because additional information was not provided by the corresponding authors on request. 28,29,[69][70][71][72][73] A total of 38 studies remained, relating to 44 independent study samples ( Figure 1).…”
Section: Search Flowmentioning
confidence: 99%
“…Seven studies were excluded because additional information was not provided by the corresponding authors on request. 28,29,[69][70][71][72][73] A total of 38 studies remained, relating to 44 independent study samples ( Figure 1).…”
Section: Search Flowmentioning
confidence: 99%
“…This is consistent with the emerging international research supporting the assertive outreach model of case management (i.e., dedicated key worker delivering intensive and flexible outreach support, providing care coordination across various relevant services and systems) to address young people's psychosocial goals (Vijverberg et al, 2017;Wilson et al, 2017). This assertive outreach model of community mental health care is particularly relevant for youth with severe and complex mental health presentations, as it is flexible, easily accessible, and actively engages and approaches young people in their own environment (Mantzouranis et al, 2019;Vijverberg et al, 2017). In contrast, integrated and centerbased "hub-like" programs similarly address key barriers as support is delivered all at the one location ("one-stopshop"), which provides streamlined support so that young people do not have to navigate a complex mental health system and referral pathways, yet it relies on their attendance at the center (Hetrick et al, 2017;Woody et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Community-based models of youth mental health care seek to increase accessibility, engagement, flexibility, and streamlining of support. Community mental health support is usually provided at a very low-or no-cost for the client, and young people are either proactively engaged in their own environment (i.e., at home) and/or supported to navigate referral pathways (Hetrick et al, 2017;Mantzouranis et al, 2019;Vijverberg et al, 2017).…”
Section: Community-based Mental Health Carementioning
confidence: 99%
“…Youth Flexible ACT provides treatment to young people with complex and severe mental health problems, who have difficulty engaging in regular mental healthcare. Practical experiences and literature indicate that these young people have a hard time accessing and remaining in regular outpatient mental healthcare 4 33 38. Several reasons for treatment disengagement in adolescents have been suggested, such as fragmented healthcare system,50 treatment discontinuity51 52 and difficulty to trust services 53.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The broader domain of Youth ACT is also limited to pre-post studies with small samples, which have reported similar positive outcomes, such as improvements in psychiatric condition,32–34 improved global functioning and increased life skills,35 and decreased number of days in hospital 35–37. Moreover, a recent Swiss study showed that Youth ACT results in improved daily functioning and clinical benefits 38…”
Section: Introductionmentioning
confidence: 99%